The Impact of Corporate Governance Quality on Principal-Agent and Principal-Principal Conflict in Indonesia - Sandra Salim; Jessica Lioe; Sandy Harianto; Yang Elvi Adelina (Jurnal Akuntansi dan Keuangan, 2022)
This study analyzes the effect of corporate governance (CG) quality on principal-agent (PA) and principal-principal (PP) conflict in Indonesia while also controlling for potential endogeneity through the use of two-stage least squares (2SLS) regression. The results for PA conflict (measured by operating expense ratio and asset utilization ratio) are consistent with the notion that better CG quality leads to a lower level of PA conflict. However, the result for PP conflict is inconclusive. While a higher CG quality is positively related to a higher dividend payout ratio, which indicates a lower PP conflict level, CG quality does not have any significant effect on wedge (difference between cash flow and control right). Moreover, further robustness tests showed that different aspects of CG have different effects on PA and PP conflict. Better CSR has a significant effect on reducing PA and PP conflict. Meanwhile, asset utilization ratio and dividend payout ratio increase due to board efficiency, internal control management, and board remuneration. Furthermore, better internal control management also leads to a lower operating expense ratio, while board remuneration reduces wedge. Interestingly, we find no significant relationship between shareholders' relation and all PA and PP conflict measures.